Glycated hemoglobin HbA1c, waist circumference, and waist-to-height ratio in overweight and obese adolescents - Elysa Nur Safrida (Paediatrica Indonesiana, 2017)
Background Central obesity has been associated with a high risk of insulin resistance. Waist circumference and waist-to-height ratio are anthropometric indices for determining central obesity and have been associated with increased blood pressure, cholesterol, and insulin levels. In adults, fat distribution around the waist is a valid predictor of glycated hemoglobin (HbA1c)levels, and is currently recommended by experts as a diagnostic tool for diabetes. Central obesity measurement has advantages over fasting blood glucose and oral glucose tolerance tests, as it is simple and inexpensive to perform.